IoT Gas Leakage Detector and Warning Generator - Alshammari, B. F.; Chughtai, M. T. (Engineering, Technology & Applied Science Research, 2020)
This paper presents an industrial monitoring system design using the Internet of Things (IoT). The gas sensor (MQ-5) captured information is posted into a data cloud. The sensor detects the leakage of gas under most atmospheric conditions. All the components are controlled by an Arduino (UNO-1) that acts as a central processor unit in the setup t. As soon as a gas leakage is detected by the sensor, the alarm is raised in the form of a buzzer. This alarm is supported by an LCD to display the location of leakage, alert the observer, and activate the exhaust fan in the particular section to extract leaked gas. The requirement of a gas detection system is not only to monitor continuously the surroundings but also to help prevent the gas leakage hence minimizing the chances of fire and damage.